Moral Emotions and Moral Motivation Beyond Childhood: discussion to the special issue - Nunner-Winkler, Gertrud; Sodian, Beate (Frontline Learning Research, 2020)
Research on the role of moral emotions in moral judgment, both in hypothetical dilemmata and in real-life moral decision making, has focused on preschool and elementary school age, with few studies spanning a larger age range, into adolescence and adulthood. The present special issue addresses a neglected area, the development of moral emotions and moral motivation in adolescence and adulthood. The focus is on the “Happy Victimizer Phenomenon”, a pattern of emotion attributions to a moral transgressor that has been primarily observed in childhood, but that does not seem to disappear with age. We begin by briefly reviewing 30 years of developmental research on moral emotion attribution and the “happy victimizer phenomenon”. This review is followed by a discussion of the present papers.